Pengaruh Knowledge Sharing Terhadap Kinerja Laboratorium Pengujian; Pelajaran Dari Implementasi Standar ISO/IEC 17025 Pada Divisi Concentrating PT. Freeport Indonesia - Kehek, Isak; Fahmi, Idqan; Najib, Mukhamad (School of Business, Bogor Agricultural University (SB-IPB), 2022)
Performance of the laboratory in general is shown by the quality of the test results that have been carried out by the laboratory, this is determined by how the laboratory can produce test results data that are technically correct and accountable. This study aims to identify the effect of knowledge sharing as a factor in increasing the performance of the testing laboratory directly or indirectly through the implementation of the ISO/IEC 17025 standard and determine strategies to improve the performance of the testing laboratory Concentrating Division of PT Freeport Indonesia. Research data were collected from 73 respondents are employees who work actively in the laboratory. The research method uses Structural Equation Modeling-Partial Least Square (SEM-PLS). The results of this study indicate that the knowledge sharing factor does not have a direct and significant effect on laboratory performance but has a significant effect through the implementation of the ISO/IEC 17025 standard. In addition, laboratory performance is positively influenced by the implementation of technical requirements which is one of the clauses of the ISO/IEC 17025 standard. The results of this study are expected to make an important contribution to the Concentrating Division management as decision and policy makers, especially for the competency development or laboratory performance by supporting the knowledge sharing process in the laboratory and understanding of ISO/IEC 17025. Keywords: ISO/IEC 17025, Knowledge sharing, Laboratory Performance, PT Freeport Indonesia, SEM-PLS